Patients' expectations and satisfaction of complete denture therapy and correlation with locus of control - Bellini, D.; Dos Santos, M. B. F.; Prisco da Cunha, V. de Paula; Marchini, L. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
P>Considering the importance of patients' satisfaction with complete denture therapy and the influence of psychosocial aspects and expectations regarding satisfaction with their dentures, the present study aimed to test for a correlation between locus of control profiles and expectations before and satisfaction after complete denture therapy. Sixty-four patients rated their expectations for aesthetic and functional results of complete denture therapy on a 10-cm visual analogue scale (VAS), using scores from 0 (worst results) to 10 (best results). A similar questionnaire was used regarding satisfaction after final denture adjustments. Patients also answered a locus of control questionnaire in the initial interview. anova and a chi-squared test were used to test for correlations among ratings, patient gender and locus of control profiles. The significance level adopted was 0 center dot 05. The expectation ratings before treatment were significantly lower than the post-treatment completion ratings, both for aesthetics (P < 0 center dot 001) and function (P = 0 center dot 004). There was no correlation between locus of control profiles and patients' ratings or between gender and VAS scores. No correlation was found between locus of control profiles and scores for expectations before and satisfaction after complete dentures.
Keywords: locus of control; patient expectations; patient satisfaction; complete dentures